The Application of Fintech and Innovation Strategies in Increasing Competitive Advantage in Pizza Hut East Medan District: Penerapan Fintech dan Strategi Inovasi dalam Meningkatkan Keunggulan Bersaing di Pizza Hut Kecamatan Medan Timur - Catherine Wijaya; Elisabeth Nainggolan (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
This study examines the influence of the application of financial technology (fintech) and innovation strategies on the competitive advantage of Pizza Hut in East Medan District. The quantitative method was used by distributing incidental questionnaires to 100 active consumers at the Medan Timur outlet, then the data was analyzed using Partial Least Squares Structural Equation Modeling to test the validity, reliability, and causality path. The results showed that fintech through the integration of e-wallet and QRIS had a positive and significant influence on competitive advantage (path coefficient 0.563, t-statistic 5.275, f² = 0.547), while product and process innovation strategies including local pizza variants, bundling packages, ordering chatbots, and real-time order tracking made a significant contribution (coefficient 0.393, t-statistic 3.646, f² = 0.267). The two variables together explain 85.3% of the variance of competitive advantage (R² = 0.853) with excellent predictive relevance (Q² = 0.844). These findings confirm that the integration of fintech capabilities with service innovation strategies is a source of sustainable competitive advantage. Practical implications include teams that can move according to their respective tasks to ensure fintech integration runs smoothly, strengthening point of sale infrastructure to connect with digital payment providers, front-line training, and optimizing promotions and menu personalization.